The perception of employee in Malaysian Maritime Enforcement Agency toward factors of corruption in public service / Muhammad Shahrul Nizam Fazil and Khairul Fitri Ab. Latib - Fazil, Muhammad Shahrul Nizam; Ab. Latib, Khairul Fitri (Faculty of Business and Management, 2014)
This study intends to study the perception of employee in Malaysian Maritime Enforcement Agency toward factors of corruption in public service. Three objectives have been set in order to achieve the purpose of the study. First objective is to study the levels of perception among employee in Malaysian Maritime Enforcement Agency toward corruption in public service. The second objective is to identify the relationship between income, technology and enforcement with corruption based on the perceptions of employee in MMEA. The third objective is to determine the most factors that influence the increases of corruption. So in order to achieve these objectives, a quantitative method is being use and data were collected by distributing 66 questionnaires to employee in MMEA Headquarters. The data were analyzed using Descriptive Analysis, Pearson Correlation Analysis and Regression Analysis. The result shows that the levels of perception among employee in Malaysian Maritime Enforcement Agency toward corruption in public service are moderate. The result for the relationship between income, technology and enforcement with corruption showed that there is a moderate relationship for each factor. The result also shows that income is the most factors that influence toward the increase of corruption based on perception of the employee of MMEA. In conclusion, this study has help in viewing the perception of the people toward corruption in Malaysia and also to identify the factor that can contribute to corruption. It is important to explore and to identify the factor in order to fight corruption.